Microtubules and microfilaments in fixed and permeabilized cells are selectively decorated by nerve growth factor. - Nasi, S (1982)
A specific antibody against nerve growth factor (NGF) and indirect immunofluorescence microscopy have been used to follow the in vitro binding of NGF to cells made permeable to large molecules. All cells tested, both target (sensory neurons and PCI2 cells) and nontarget (3T3, BKH 2I, C6 glioma cells), revealed a decoration of cytoskeletal structures which on the basis of their form, reactivity with antibodies, and sensitivity to specific drugs may be identified as microtubules (MTs) and microfilaments (MFs). The decoration of either structure depends on the fixation and permeabilization conditions: MFs, in the form of stress fibers, are stained by NGF when the plasma membrane is permeabilized with methanol/acetone; MTs become intensely stained when the plasma membrane is solubilized with a nonionic detergent in the presence of a MT-stabilizing medium. The two procedures do not affect the staining of these structures with specific antibodies. Binding of 125I-labeled NGF to PCI2 cells was not competitively inhibited by a 100-fold excess of several positively charged proteins but it was markedly decreased in the presence of DNase I. 125I-Labeled NGF interacted with MTs and F-actin (fixed with paraformaldehyde) in a range of concentrations similar to that used for their cellular localization with NGF-anti-NGF. Our studies show that the specificity and affinity of NGF binding to MTs and MFs is in the range of that of antibodies against tubulin and actin. The possible relevance of these findings to the mechanism of action of NGF in target cells is discussed.